2007
DOI: 10.1371/journal.ppat.0030080
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Link between Malaria and Epstein–Barr Virus Reactivation

Abstract: Although malaria and Epstein–Barr (EBV) infection are recognized cofactors in the genesis of endemic Burkitt lymphoma (BL), their relative contribution is not understood. BL, the most common paediatric cancer in equatorial Africa, is a high-grade B cell lymphoma characterized by c-myc translocation. EBV is a ubiquitous B lymphotropic virus that persists in a latent state after primary infection, and in Africa, most children have sero-converted by 3 y of age. Malaria infection profoundly affects the B cell comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
114
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(119 citation statements)
references
References 34 publications
3
114
1
1
Order By: Relevance
“…This apparently contrasts the recent findings by Chene et al (2007), who showed that P. falciparum CIDR1a might bind to Akata cells in vitro and lead to an increase in the number of cells switching to the viral lytic phase. Nevertheless, the data can be reconciled given that access of hemozoin and CIDR1a to B cells in vivo and the proposed mechanisms of action of the two compounds are distinct.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This apparently contrasts the recent findings by Chene et al (2007), who showed that P. falciparum CIDR1a might bind to Akata cells in vitro and lead to an increase in the number of cells switching to the viral lytic phase. Nevertheless, the data can be reconciled given that access of hemozoin and CIDR1a to B cells in vivo and the proposed mechanisms of action of the two compounds are distinct.…”
Section: Discussioncontrasting
confidence: 99%
“…Nevertheless, the data can be reconciled given that access of hemozoin and CIDR1a to B cells in vivo and the proposed mechanisms of action of the two compounds are distinct. CIDR1a is expressed at the surface of infected erythrocytes, and direct contact between erythrocytes and B cells is required to show a posited mechanism similar to BCR crosslinking (Chene et al, 2007). In contrast, hemozoin is shed in large amounts after schizont rupture, is not bound to erythrocytes, and thus may disperse more broadly, and be taken up by immune cells in the absence of direct contact with erythrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…EBV persists in a latent state in resting memory B cells that circulate in the peripheral blood (Thorley-Lawson 2001). The exposure of B cells to malarial antigens during multiple infectious episodes could reactivate the virus from memory B cells, thereby increasing viral load and the number of EBV-infected cells (Donati et al 2006;Chene et al 2007).…”
Section: Epidemiology Of Ebl: the Role Of Infectious Agents In The Pamentioning
confidence: 99%
“…7 eBL is hypothesized to be of a multifactorial etiology, encompassing environmental factors, infectious factors (i.e., EBV and malaria infection), immune system disturbances, and potentially, host genetic predisposition. 2,8,9 Although the precise pathogenic mechanisms for eBL have not been fully elucidated, genetic susceptibility has been found to play an important role in the development and progression of BL. 10,11 Polymorphisms in cytokine genes can influence inflammation and immune response to infection and may be related to risk of eBL, 12,13 but they have yet to be well-investigated within the context of epidemiologic studies.…”
Section: Introductionmentioning
confidence: 99%